Hepcidin Increases Cytokines in Alzheimer’s Disease and Down’s Syndrome Dementia: Implication of Impaired Iron Homeostasis in Neuroinflammation - Raha, Animesh Alexander; Ghaffari, Seyedeh Deniz; Henderson, James; Chakraborty, Subhojit; Allinson, Kieren; Friedland, Robert P.; Holland, Anthony; Zaman, Shahid H.; Mukaetova-Ladinska, Elizabeta B.; Raha-Chowdhury, Ruma (Frontiers in Aging Neuroscience, 2021)
The liver-derived hormone hepcidin, a member of the defensin family of antimicrobial peptides, plays an important role in host defense and innate immunity due to its broad antibacterial and antiviral properties. Ferritin, an iron storage protein is often associated with iron deficiency, hypoferritinemia, hypoxia, and immune complications, which are all significant concerns for systemic infection in Alzheimer’s disease (AD) and Down’s syndrome (DS) dementia. Serum and post-mortem brain samples were collected from AD, DS and age matched control subjects. Serum samples were analyzed with ELISA for ferritin, hepcidin and IL-6. Additionally, post-mortem brain sections were assessed by immunohistochemistry for iron-related and inflammatory proteins. A significant increase in serum hepcidin levels was found in DS, compared to controls and AD subjects (p < 0.0001). Hepcidin protein was visible in the epithelial cells of choroid plexus, meningeal macrophages and in the astrocytes close to the endothelium of blood vessels. Hepcidin co-localised with IL-6, indicating its anti-inflammatory properties. We found significant correlation between hypoferritinemia and elevated levels of serum hepcidin in AD and DS. Hepcidin can be transported via macrophages and the majority of the vesicular hepcidin enters the brain via a compromised blood brain barrier (BBB). Our findings provide further insight into the molecular implications of the altered iron metabolism in acute inflammation, and can aid towards the development of preventive strategies and novel treatments in the fight against neuroinflammation.